CEO overconfidence and stock price crash risk - KIM, Jeong-Bon (Institutional Knowledge at Singapore Management University, 2016)
This study examines the association between chief executive officer (CEO) overconfidence and future stock price crash risk. Overconfident managers overestimate the returns to their investment projects and misperceive negative net present value (NPV) projects as value creating. They also tend to ignore or explain away privately observed negative feedback. As a result, negative NPV projects are kept for too long and their bad performance accumulates, which can lead to stock price crashes. Using a large sample of firms for the period 1993–2010, we find that firms with overconfident CEOs have higher stock price crash risk than firms with nonoverconfident CEOs. The impact of managerial overconfidence on crash risk is more pronounced when the CEO is more dominant in the top management team and when there are greater differences of opinion among investors. Finally, it appears that the effect of CEO overconfidence on crash risk is less pronounced for firms with more conservative accounting policies.